(untitled) (Ustozlar uchun, 2026)
For the surgical treatment of gallbladder disorders, laparoscopic cholecystectomy (LC) has emerged as the gold standard in recent years. However, a review of the literature shows that there is still a considerable risk of problems, especially bile leakage. Materials and Methods: With a focus on cystic duct management strategies during LC, this research examined scholarly literature, including original papers, systematic reviews, and meta-analyses. Comparing contemporary approaches, including vessel-sealing devices, with conventional ligation and clipping procedures received special attention.